2017
DOI: 10.1039/c7ce00505a
|View full text |Cite
|
Sign up to set email alerts
|

From nanoparticles to bulk crystalline solid: nucleation, growth kinetics and crystallisation of mixed oxide ZrxTi1−xO2 nanoparticles

Abstract: We describe the preparation of mixed metal oxide nanoparticles of a desirable composition and their transformation to the crystalline solids ZrxTi1−xO2 (0.0 ≤ x ≤ 1.0) after heat treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In particular, it increases from 3.2 nm to 3.6 nm when x increases from 0 to 0.2, than passing a plateau of ∼4.2 nm (0.3≤x≤0.7) it decreases to 3.6 nm for x=1. After the heat treatment, these ZTOA nanoparticles undergo structural reorganization (i) becoming first amorphous ZTOA → a ‐Zr x Ti 1‐x O 2 at T 1 =210‐250 °C following by crystallization a ‐Zr x Ti 1‐x O 2 → crystalline ‐Zr x Ti 1‐x O 2 at T 2 =380‐680 °C, where both temperatures T 1 and T 2 were strongly sensitive to the elemental composition x. We observed that in the range of the elemental compositions x≤0.2, Zr x Ti 1‐x O 2 conserves anatase crystalline phase.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…In particular, it increases from 3.2 nm to 3.6 nm when x increases from 0 to 0.2, than passing a plateau of ∼4.2 nm (0.3≤x≤0.7) it decreases to 3.6 nm for x=1. After the heat treatment, these ZTOA nanoparticles undergo structural reorganization (i) becoming first amorphous ZTOA → a ‐Zr x Ti 1‐x O 2 at T 1 =210‐250 °C following by crystallization a ‐Zr x Ti 1‐x O 2 → crystalline ‐Zr x Ti 1‐x O 2 at T 2 =380‐680 °C, where both temperatures T 1 and T 2 were strongly sensitive to the elemental composition x. We observed that in the range of the elemental compositions x≤0.2, Zr x Ti 1‐x O 2 conserves anatase crystalline phase.…”
Section: Resultsmentioning
confidence: 88%
“…Previous studies have shown that an addition of Zr to TiO 2 increases its specific surface area. That of Zr x Ti 1‐x O 2 solids often peaked at x=0.5, which however referred to amorphous or non‐crystalline materials, since heat treatment temperatures applied were lower than that of crystallization T c (x=0.5)=650 °C: 550 °C,, 400 °C, 500 °C, and 402 °C . The compositions heat treated with T>T c (x) have shown the highest surface areas at x=0.5 and x=0.25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of a stable nucleus becomes in this connection of a particular importance, since it designates the ultimate species capable to withstand the 5 restructuring and link to the bulk crystalline solids properties. In support of this statement, correlations between the nucleus composition, size, phase transformation temperature and crystalline phase have been demonstrated in bicationic zirconium-titanium oxo-alkoxy (ZTOA) species [19]. It is also intriguing that the nucleus size of TOA species corresponds to the smallest size of TiO 2 crystallites R=1.5 nm, which electronic band structure converges to that of the bulk TiO 2 solid [20][21].…”
Section: Introductionmentioning
confidence: 86%
“…This model has been initially proposed for TOA species ascribing =2n-k-1 and =+1 with the solution in integer values n=3 and k=2 [12]. Later on, the validity of the model has been confirmed for ZOA [13] and mixed oxide ZTOA [19] species.…”
mentioning
confidence: 98%